Calls made to the Poisons Information Centre reveal need for improved risk management of cleaning agents in the workplace. Issue 1 (2nd January 2020) - Schenk, Linda; Feychting, Karin; Annas, Anita; Öberg, Mattias
Abstract : Purpose . This study aimed to investigate chemical injuries caused by cleaning agents and disinfectants by reviewing poison control data. Methods . We performed a 5-year retrospective analysis of calls to the Swedish Poisons Information Centre (PIC) concerning occupational use of cleaning agents and disinfectants. In addition, callers for 17 new cases were interviewed. Results . Out of 8240 occupationally related cases handled by the PIC during 2010–2014, 24% concerned cleaning agents and disinfectants ( N = 1983). Of these, one-third were classified as major risk cases, generally due to potential for corrosive eye and skin injuries. The most frequent type of workplace was restaurants and caterers. However, information about occupation was only identifiable for 30% of the cases. Follow-up interviews exemplify how limited awareness of safety data sheets and disregard of protective equipment may contribute to health-related outcomes such as absence at work. Conclusions . Management and prevention strategies for cleaning agents should be improved. PIC records hold relevant information both for designing interventions and for future research on occupational health and safety management. We suggest that systematic collection by the PIC of information on occupation and age would further improve the usefulness for occupational injury surveillance purposes.